The Effects of Dokhwalgisaeng-tang against Disuse Muscle Atrophy in Gastrocnemius of Rats - Han Mi Gong; Yun Kyu Lee; Bong Hyo Lee; Jae Soo Kim; Hyun-Jong Lee (MEDrang Inc., 2018)
Background The purpose of this study was to examine the effect of Dokhwalgisaeng-tang on immobilization-induced muscle atrophy. Methods Twenty young male Sprague-Dawley rats were divided into 2 groups. The rats in Dokhwalgisaeng-tang group were orally administered Dokhwalgisaeng-tang water extract, and the rats in the control group were given saline only. Hind limb immobilization was performed with casting tape to keep the left ankle joint in a fully extended position. No intervention was performed on the right leg which was used as an intact region. After 2 weeks of immobilization, all animals were sacrificed, and the gastrocnemius muscle was dissected from both legs and weighed. The morphology of the right and the left gastrocnemius muscle in both the Dokhwalgisaeng-tang and the control group was assessed by hematoxylin and eosin staining. The muscle cross sectional area was examined by image analysis (Axiovision LE software). In addition, immunohistochemical staining was carried out using the free-floating method, and the number of apoptotic related proteins were counted (anti-BAX, anti-Bcl-2). Results Dokhwalgisaeng-tang showed a significant protective effect against the reduction of the left gastrocnemius muscle (weight and muscle cross sectional area) compared with the control group. Moreover, the treatment with Dokhwalgisaeng-tang significantly reduced protein expression of BAX and increased protein expression of Bcl-2 in the gastrocnemius muscle compared with the control group. Conclusions Dokhwalgisaeng-tang showed protective effects against disuse muscle atrophy, potentially through altered BAX and Bcl-2 protein expression in the gastrocnemius muscle.